Optimizing the health of the elderly through screening and health education - Yoga Tri Wijayanti; Deviarbi Sakke Tira; Anita Lontaan; Suprapto Suprapto; Agnes Montolalu (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2024)
The increasing number of older adults in Indonesia demands more attention to efforts to optimize their health. The elderly are susceptible to various chronic and degenerative diseases that can reduce the quality of life. Therefore, a comprehensive approach through screening and health education is urgently needed to improve the health status of older adults. This community service aims to conduct health screenings and provide health education to older adults in certain areas. The methods used include basic health checks such as blood pressure, blood sugar, and body mass index (BMI), as well as counseling on healthy lifestyles, nutrition, and the importance of physical activity. The results of this activity show that many older adults are not aware of their actual health conditions. Through screening, several cases of hypertension, diabetes, and obesity were found that required further treatment. In addition, the health education provided is able to increase the knowledge and awareness of older adults regarding the importance of maintaining a healthy lifestyle. This community service concludes that the combination of screening and health education is effective in detecting health problems and increasing the awareness of the elderly about the importance of prevention and early treatment. Recommendations for similar programs in the future are to expand the reach of activities, strengthen collaboration with local health facilities, and develop more comprehensive educational materials